Надежность жидкометаллических индукционных МГД машин - Абхази Вахтанг Вадимович (Энергия, 1972)
Экземпляры: КХ (20120411) / Инвентарный номер: 546290 / Цена: 0.55 / Сис.шифр: 621.3 / Авт.знак: А 17 / ГРНТИ: 53 / ББК: 34